2017
DOI: 10.1038/srep40556
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 is upregulated in ascites in patients with spontaneous bacterial peritonitis

Abstract: MircoRNA’s (miR) have been recognised as important modulators of gene expression and potential biomarkers. However, they have been rarely investigated in bio fluids apart from blood. We investigated the association of miR-125b and miR-155 with complications of cirrhosis. Ascites was prospectively collected from patients with cirrhosis undergoing paracentesis at our department. miR’s were determined in the supernatant using qPCR and normalized by SV-40. Clinical parameters were assessed at paracentesis and duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
(59 reference statements)
4
8
0
Order By: Relevance
“…In the present study, serum levels of miRNA 155 &146b were found to be significantly higher in spontaneous bacterial peritonitis patients than that in ascites patients not complicated by spontaneous bacterial peritonitis infection. This goes in agreement with the findings of a study by Lutz et al, 2017, who found that miR-155 was significantly upregulated during spontaneous bacterial peritonitis when compared to ascites patients without spontaneous bacterial peritonitis infection [14]. Moreover, Jiménez-Alesanco et al 2019, initiated a study aimed to specify the different types of exosomes released by the pancreas to the pancreatitis-associated ascitic fluid as well as those circulating in plasma in an experimental model of acute pancreatitis in rats.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, serum levels of miRNA 155 &146b were found to be significantly higher in spontaneous bacterial peritonitis patients than that in ascites patients not complicated by spontaneous bacterial peritonitis infection. This goes in agreement with the findings of a study by Lutz et al, 2017, who found that miR-155 was significantly upregulated during spontaneous bacterial peritonitis when compared to ascites patients without spontaneous bacterial peritonitis infection [14]. Moreover, Jiménez-Alesanco et al 2019, initiated a study aimed to specify the different types of exosomes released by the pancreas to the pancreatitis-associated ascitic fluid as well as those circulating in plasma in an experimental model of acute pancreatitis in rats.…”
Section: Discussionsupporting
confidence: 87%
“…MiRNAs regulate gene expression by binding to messenger RNA (mRNA), leading to posttranscriptional changes by targeting the 3'-UTR of mRNA to down-regulate gene expression [13]. MiRNAs are considered one of the potential biomarkers for a variety of diseases, including inflammatory liver diseases [14], because of their minute size and ability to circulate [15]. They are stable and therefore can be detected in plasma or serum, which made them an uprising potential biomarker for diagnosis and prognosis.…”
Section: Mirnas As Biomarkersmentioning
confidence: 99%
“…Regarding liver diseases it has been widely reported that miRNAs are dysregulated in the liver, and they are described as being involved and playing an important role in the pathophysiology of liver diseases [13][14][15][16]. Moreover, they can be used as biomarkers [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Data from another study, using blood samples from cirrhosis patients with ascites, showed that miR-155 was a good diagnostic marker for SBP, and a greater efficiency in diagnosis was achieved by detecting both serum CD64 and calprotectin levels [ 62 ]. Furthermore, in studies examining ascites miRNA levels in patients with cirrhosis, miR-155 [ 61 ] and miR-223 [ 106 ] were elevated in patients with SBP, indicating that these miRNAs might be involved in the local immune response during SBP.…”
Section: Micrornas and Immune Response Against Bacterial Infectionmentioning
confidence: 99%